2019
DOI: 10.1111/bjh.15906
|View full text |Cite
|
Sign up to set email alerts
|

Citrullinated histone H3, a biomarker for neutrophil extracellular trap formation, predicts the risk of mortality in patients with cancer

Abstract: Summary Prior studies indicate that neutrophil extracellular traps ( NET s) are associated with arterial thromboembolism ( ATE ) and mortality. We investigated the association between NET formation biomarkers (citrullinated histone H3 [H3Cit], cell‐free DNA [cfDNA], and nucleosomes) and the risk of ATE and all‐cause mortality in patients with cancer. In this prospective cohort study, H3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(59 citation statements)
references
References 62 publications
(88 reference statements)
2
56
0
1
Order By: Relevance
“…Citrullinated histone H 3 and histone-DNA complex are parts of neutrophil extracellular traps (NETs), released from acute inflammation and neutrophil apoptosis and necrosis. These NETs are formed after citrullination of histones by activation of protein arginine deiminase 4, which has been associated with thrombosis in patients with cancers [ 40 , 41 ]. Leukocytes are known to release nuclear contents that form these extracellular traps, which are mainly composed of the histone-DNA complex [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Citrullinated histone H 3 and histone-DNA complex are parts of neutrophil extracellular traps (NETs), released from acute inflammation and neutrophil apoptosis and necrosis. These NETs are formed after citrullination of histones by activation of protein arginine deiminase 4, which has been associated with thrombosis in patients with cancers [ 40 , 41 ]. Leukocytes are known to release nuclear contents that form these extracellular traps, which are mainly composed of the histone-DNA complex [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although there are caveats with associating NETs and human disease, the sheer number of recent findings in this area underscores the importance of strictly regulated neutrophil activation and turnover (safe removal) to health and homeostasis. For example, NETs have been associated with multiple types of cancer and cancer metastasis 39 , 40 , including breast cancer 41 , hepatocellular carcinoma 42 , lung cancer 43 , ovarian cancer 44 , oral squamous cell carcinoma 45 , pancreatic cancer 46 , and thyroid cancer 47 . NETs have been implicated in autoimmune disorders such as lupus erythematosus 48 51 and in the development of thrombosis 52 54 and can contribute to the severity of sepsis 55 , 56 .…”
Section: Nets and Human Diseasementioning
confidence: 99%
“…The degradation or inhibition of NETs by DNAse-1 or neutrophil elastase (NE) inhibitor has been demonstrated to prevent metastasis in a murine cecal ligation and puncture model ( 15 ). Citrullinated histone H3 (cit-h3; a NETs activation marker) is detectable in the plasma of patients with advanced cancer, and can serve as a distinct prognostic marker that is associated with a poor clinical outcome in numerous types of tumor ( 16 ). After deposition of NETs was found to be significant in malignant tumors, it was also identified that NETs increase the risk of thrombosis in patients with cancer, which may be associated with a poor prognosis ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%